TOEFL, Cultural Bias and Latin Background - Carvalho, Heitor Garcia de; Gariglio, Maria Inês; Melo, Sidney Carlos de (The ESPecialist, 2012)
Through a validity analysis of a TOEFL sample applied to Brazilian undergraduates, the linear relationship between their scores and silent reading of authentic, technicalscientific texts was rejected. Thus, its uset as co-variate in the statistical analysis has been discarded and a more complex model of variables has been postulated.